Determination of the Chemical Stability of Various Formulations of Tobramycin Eye-Drops by HPLC Method and Data Analysis by R-GUI Stability Software - María Ana Rosasco, Adriana Inés Segall (Journal of Applied Pharmaceutical Science, 2015)
Tobramycin, is a water soluble aminoglycoside antibiotic produced by the fungus Streptomyces tenebrarius and used in a variety of pharmaceutical applications including ophthalmic solutions, suspensions and ointments; inhalation solutions and intravenous administration. There are commercially available eye drops formulations in the Argentinian market that have different conservation conditions. We formulated six eye drops solutions, studied their stability at 2-8°C, 25°C, and 40°C, 75% RH and quantified using USP method. Only half of the formulations studied were found to be stable for two years at ambient temperature which is their expected expiry date and only one for three years in the same condition. One system was unstable in the three conservation conditions studied, including appearance and pH.
Keywords: Tobramycin, eyes-drops, stability, software generated shelf life, formulations.